The Economic Costs of Structural Separation, Line of Business Restrictions, and Common Carrier Regulation of Online Platforms and Marketplaces: A Quantitative Evaluation - Christian M. Dippon; Matthew D. Hoelle (International Telecommunications Society (ITS), 2022)
Online platforms and marketplaces are services that bring consumers and producers together via the internet by providing consumers direct and instantaneous access to an extensive array of global goods and services and by enabling producers to reach consumers largely untethered by size and geographic reach. The popularity of online platforms and marketplaces attests to the societal benefits these services offer to consumers and producers alike. However, some US lawmakers and competition authorities believe that the growth of these platforms is a threat to competition. To remedy this perceived threat, some lawmakers in the House of Representatives and the Senate introduced several bills that would effectively subject certain companies to common carrier, structural separation, and line of business restrictions. The proposed bills differ in several important aspects, but they all seek to regulate online platforms and marketplaces larger than a certain size threshold. Although there is extensive media coverage and public debate on these bills, no one has addressed the actual scope and economic impact on consumers, businesses, and the overall US economy. Our analysis demonstrates that if the bills are enacted they would impose 319 billion in costs on Google, Apple, Facebook, Amazon, and Microsoft. These companies, in turn, would pass these costs through to consumers and business users via higher retail prices and reduced service offerings. Consumer effects are analyzed using a consumer survey to measure the lost consumer welfare for one illustrative service, Amazon Prime membership. We find that consumers would lose 22 billion in consumer welfare per year if Amazon would be forced to discontinue or reduce the services presently included in the Amazon Prime membership to comply with the bills. Our analysis also demonstrates that the bills impact far more companies than the primary targets-Google, Apple, Facebook, Amazon, and Microsoft. Rather, the bills would directly constrain at least 13 additional companies that operate online platforms in the short term. The proposed legislation would impact foreign companies doing business in the United States significantly less than US companies given the US-specific nature of the bills' primary size thresholds. Thus, the total economic costs of the bills stand to far exceed the numbers we calculated for the primary targets. Moreover, we find that adjusting the size threshold for inflation does not reduce the bills' economic costs. The market capitalization of the largest US publicly traded companies has historically grown much faster than inflation, which largely obviates any adjustment, and implies that over the next decade there could be well over 100 US companies that must change their strategies and business models because of these bills. The bills would not achieve the stated goals of their proponents as they would have no beneficial effect on inflation and likely deleterious effects on innovation. With regards to inflation, 96 percent of the most influential economists at leading US universities do not agree with the claim that antitrust interventions could successfully reduce US inflation over the next 12 months. The overwhelming consensus among economists is that regulatory measures in the proposed bills would be a poor substitute for fiscal and monetary policy and therefore unlikely to have any significant effect on inflation.
Keywords: L11; L12; L41; O31; J18; L86; 330; online platform regulation; competition analysis; international competitiveness; regulation